2022
DOI: 10.1108/jeas-12-2021-0254
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public legal protection on the internal corporate governance efficiency in banking sector

Abstract: PurposeThe purpose of this research is to reveal the impact of public legal protection on the efficiency of internal corporate governance in banks. In addition, this research proposes a new corporate governance index that could be employed by the banking sector to evaluate the performance of their internal corporate governance mechanisms.Design/methodology/approachOrbis database, annual reports and direct questionnaire are used to collect corporate governance data of 127 banks from 14 countries during 2020. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…The findings shows that neither of the electronic payment transaction values are significantly related to RevGrowth it . This is opposes to the findings of the previous studies by El-Chaarani and El Abiad (2018) and Aduda and Kingoo (2012), however, those findings are based on non-Asian bank sample. Simpson (2002) justified that electronic payment generate higher revenue for banks in countries with strong information technology framework.…”
Section: Regression Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings shows that neither of the electronic payment transaction values are significantly related to RevGrowth it . This is opposes to the findings of the previous studies by El-Chaarani and El Abiad (2018) and Aduda and Kingoo (2012), however, those findings are based on non-Asian bank sample. Simpson (2002) justified that electronic payment generate higher revenue for banks in countries with strong information technology framework.…”
Section: Regression Resultscontrasting
confidence: 99%
“…The diffusion of ICT technologies has fostered the expansion of e-commerce, banking, finance and payment systems. This forced bank to change the way providing financial products and services in this modern era to survive in the highly competitive market (El-Chaarani & El Abiad, 2018). Sujud and Hachem (2017) revealed that bank innovation positively affects bank's profitability and return on assets (ROA).…”
Section: Theoretical Review On Technology Innovation and Bank Perform...mentioning
confidence: 99%
“…The role of this index is to provide bankers a tool to monitor the efficiency of their corporate governance designs. This is quite different to other approaches relying on public legal protection for example [ 14 ]. Whereas such indices rely on factors such as transparency, accountability, and risk management, our index focuses on the efficiency of the corporate governance designs.…”
Section: Introductionmentioning
confidence: 72%
“…In case of banks, Vicente-Ramos et al [ 15 ] and El-Chaarani and El-Abiad [ 14 ], argued that the existence of efficient corporate governance is an important tool to reduce the agency conflicts that could occur between debtholders, managers, and owners. They stated that managers and manager-owners can select risky investments and strategies to raise their private benefits without considering the interests of external owners and debtholders.…”
Section: Definition Of the Internal Corporate Governance Indicators I...mentioning
confidence: 99%
See 1 more Smart Citation